In vivo evaluation of optic nerve aging in adult rhesus monkey by diffusion tensor imaging - Yan, Yumei; Li, Longchuan; Preuss, Todd M.; Hu, Xiaoping; Herndon, James G.; Zhang, Xiaodong (Quantitative Imaging in Medicine and Surgery, 2014)
Aging of the optic nerve can result in reduced visual sensitivity or vision loss. Normal optic nerve aging has been investigated previously in tissue specimens but poorly explored in vivo. In the present study, the normal aging of optic nerve was evaluated by diffusion tensor imaging (DTI) in non-human primates. Adult female rhesus monkeys at the ages of 9 to 13 years old (young group, n=8) and 21 to 27 years old (old group, n=7) were studied using parallel-imaging-based DTI on a clinical 3T scanner. Compared to young adults, the old monkeys showed 26% lower fractional anisotropy (P